Efektivitas Pendekatan Student Centered Learning yang Berbasis ICT untuk Meningkatkan Kemampuan Apresiasi Prosa Fiksi Peserta Didik - Yasnur Asri (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2012)
This study aims at finding out the effectiveness of ICT based Student Centered Learning Approach based on ICT toward prose appreciation ability of students at Indonesian Department UNP. The population was 141 students classified into four classes at sixth semester at 2011/2012 academic year. By clustering random sampling, class C with 36 students was assigned as the experimental group, and class D with 36 students was assigned as the experimental group. The design of this study was controlled-group pretest to posttest to find out students’ prose appreciation ability. At the beginning of this study, both groups were normally distributed; indicated by the same variety and there is no significant difference in their abilities at prose appreciation. The finding of this study revealed that there was a difference of their abilities at prose appreciation. The calculation, tobs (7,5072) >ttable (2,0301) showed that students at experimental group, who used ICT based Student Centered Learning Approach, achieved the passing grades. While the control group with the calculation of tobs (-0,3241) <ttable (2,0301), the students could not achieve the passing grades. This means that ICT based Student Centered Learning Method effectively improves students’ ability at prose appreciation. Keywords: approach, student centered learning, ICT, ability, prose appreciation.